2021
DOI: 10.2355/isijinternational.isijint-2021-275
|View full text |Cite
|
Sign up to set email alerts
|

TTP Diagrams of Graphitization of Creep Ruptured Carbon Steels and 0.5Mo Steel

Abstract: Graphitization in carbon steels should be avoided because it results in the degradation of material performance. Safety management standards state that graphitization occurs at 698 K for carbon and carbon-Mo steels, although some standards state it to be above 738 K for carbon-Mo steels. However, recently, graphitization was found at 673 K in creep ruptured 0.3C steel. Herein, we investigated the graphitization behavior of creep ruptured 0.3C, 0.2C, and 0.5Mo steels. It was confirmed that the graphitization oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 21 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…[19][20][21] Their graphitization behavior has been systematically investigated in our previous studies. 13,14) The graphitization condition in the gauge and grip portions for the steels are summarized in Fig. 1 and Fig.…”
Section: Data For Predictionmentioning
confidence: 99%
See 4 more Smart Citations
“…[19][20][21] Their graphitization behavior has been systematically investigated in our previous studies. 13,14) The graphitization condition in the gauge and grip portions for the steels are summarized in Fig. 1 and Fig.…”
Section: Data For Predictionmentioning
confidence: 99%
“…12) Recently, Hatakeyama et al systematically investigated the graphitization behavior of carbon steels and 0.5Mo steel using creep ruptured specimens obtained through the NIMS Creep Data Sheet Project. 13,14) They established the TTP diagram of these steels and pointed out that graphitization behavior changes with, not only time and temperature, but also the chemical composition of the steels. 14) In addition, they discovered two types of graphite, i.e., elongated and spherical graphite, and suggested that elongated graphite formation is especially accelerated by applied stress.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations